Effect of different concentrate levels in the pre and post parturition period on milk production and body score of dairy cows - Salmazo, Rafael; Mizubuti, Ivone Yurika; Ribeiro, Edson Luis de Azambuja; Pereira, Elzânia Sales; Moreira, Fernanda Barros; Rocha, Marco Antonio da; Seneda, Marcelo Marcondes; Hiroki, Paulo Tadatoshi; Krawulski, Cristina Célia (Semina: Ciências Agrárias, 2012)
This experiment was carried out with the objective of evaluating the effects of different levels of concentrate supplement in the pre and post-parturition periods on milk production and body score of dairy cow. 54 cows in a completely randomized design, distributed in 3 x 2 factorial arrangement, with 3 treatments, 2 periods and 9 repetitions for treatment, were used. The treatments with different levels of concentrate supplement (in dry basis) in the pre-parturition periods (PRE), were: PRE1 = 0% of the body weight (BW); PRE2 = 0.5% of the BW; PRE3 = 1.0% of the BW; and in the post-parturition (POS), were: POS1 = 1kg for each 2.5 kg of produced milk; POS2 = 1kg for each 2.0kg of produced milk and POS3 = 1kg for each 1.5kg of produced milk, above 6 kg of milk a day. The milk weight and body condition scores were evaluated every seven days. There was not significant difference among the treatments of PRÉ period for milk production, however, it was verified that the increase in the PRE supplementation, improved the average body condition of animals in post parturition period. In the treatments of POS period, there was positive and increasing effect with the increasing supplementation level, on milk production and medium body score of the animals. Improvement was not observed in the milk production with the increase of supplement in the PRE period, but in the POS period there was higher milk production with the increase supplement. There were not correlation among pre-parturition treatments and milk production, but there was correlation of these with body score to the parturition (r=0.66). There was correlation of supplement levels in the post parturition with medium body score (0.36) and with milk production (0.32). It can be concluded that the increasing supplement level in the pre-parturition period improves the body score but not the milk production of the animals. The increase of supplement in the post parturition period gets better so much the body score as the milk production.